Influence of the type of work shift in Female Sexual Function Index of healthcare sector female workers. (March 2017) - Valenzuela-Peters, Romina; Contreras-García, Yolanda; Manriquez-Vidal, Camilo
Abstract: Objective: To determine the influence of the type of work shift over the sexual function of healthcare sector female workers. Methodology: Quantitative, cross-sectional and correlation type of study. Universe composed of a high complexity hospital female workers aged between 20 and 64 years old who worked in Day Shifts (DS) and Rotating Shifts (RS). Bio-social-demographic profile of 365 female workers was characterized by means of the Female Sexual Function Index (FSFI). Statistical analysis was carried out using SPSS v.19.0 Software and univariate, bivariate and multivariate analyses were applied. Mann-Whitney's non-parametric test was employed, altogether with Chi Square Test, Fisher's exact test and logistic regression with p-value < 0.05. Results: 36, 5 years old mean age (10, 65 SD); 43, 2% belongs to DS and 56, 7% belongs to RS. General FSFI scored 27, 86 points (6, 11 SD), with an mean of 27, 47 points (6, 82 SD) for DS and 28, 16 points (5, 51 SD) for the RS. Variables that might affect FSFI in the case of RS were the Health Service Assistant category, with 7, 11 OR; 2, 051–24, 622 IC; p = 0, 002 and chronic disease with 2, 226 OR; 1093–4533 IC; p = 0, 027. Protective variables for DS, the use of hormonal contraceptive method with 0, 322 OR; 0, 145–0, 713 IC; p = 0, 005 and non- hormonal contraceptive method with 0, 229 OR; 0, 09–0, 586 IC; p = 0, 002. Conclusion: There was no significant FSFI difference per shift. A protective factor for DS and two Risk factors for RS were identified.